Case Report : Management of Closed Pyometra on a 7 Year Old Bitch - Mey Vanda Pusparina Sajida; Muhammad Rizqi Fadhli (Media Kedokteran Hewan, 2023)
Pyometra commonly occurs in female dogs > 4 years of age. There are two types of pyometra: open pyometra and closed pyometra. Open pyometra referred to purulent and bloody discharge from the vulva, while closed pyometra did not have any vaginal discharge; however, there was an enlarged abdomen from the fluid-filled uterus. A 7-year-old domestic bitch with a swollen abdomen was clinically diagnosed with closed pyometra as there was no vaginal discharge. Additional examinations, such as radiography, complete blood count, and biochemistry profiles were also performed to establish the diagnosis. A clear mass with grayish features, characteristic of fluid-filled abdomen, was found on radiography, while complete blood examination showed leukocytosis and elevated globulin levels, indicating an infection. Based on the following examinations, ovariohysterectomy was performed to eliminate the source of infection. Anti-inflammatory and antibiotic drugs were administered post-surgery, and the patient fully recovered after one week of intensive care.